Characterization of the Fruits and Seeds of Alpinia Oxyphylla Miq by High-Performance Liquid Chromatography (HPLC) and near-Infrared Spectroscopy (NIRS) with Partial Least-Squares (PLS) Regression. (23rd July 2020) - Li, Rong; Zeng, Canbiao; Li, Junni; Zhu, Kailian; Lin, Xinxin; Wen, Jingfeng; Guo, Huanjia; Weng, Wenfeng; Wang, Dong; Ji, Shengguo
Abstract: Comprehensive quality control provides powerful tools to assure the quality of drugs and reap their therapeutic effects. The present study aimed to develop methods for the measurement of nootkatone, the alcohol-soluble extract, the water-soluble extract, the essential oil extract, moisture, and total ash content of the fruits and seeds of Alpinia oxyphylla Miq. using near-infrared spectroscopy (NIRS), a technique that has been particularly useful for the rapid and simultaneous evaluation of plant constituents. The nootkatone levels in the fruits and seeds of A. oxyphylla were determined by high-performance liquid chromatography (HPLC), while the other parameters were assayed by the standard methods described in the 2015 Edition of the Chinese Pharmacopeia. Twelve qualitative models were developed by the use of partial least-squares (PLS) regression. The correlation coefficients of calibration for nootkatone, moisture, alcohol-soluble extractive, water-soluble extractive, essential oil extractive, and the total ash content of the fruits and seeds ranged from 0.9372 to 0.99433. The root mean square error of validation varied from 0.00163 to 0.0307. The obtained results indicate that the established models were reliable and accurate for assaying the twelve components of the fruits and the seeds. Moreover, NIRS was demonstrated to be useful for the development of quality standards for A. oxyphylla and for its routine screening, rapid analysis, and quality assessment.